Answered

Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

x-(9x-10)+11=12x+3(-2x+1/3)

Sagot :

heyDB
Simplify each term.
x−(9x−10)+11=12x−6x+1

Add 12x and −6x to get 6x.
x−(9x−10)+11=6x+1

Simplify each term.
x−9x+10+11=6x+1

Add x and −9x to get −8x.
−8x+10+11=6x+1

Add 10 and 11 to get 21.
−8x+21=6x+1

Move 6x to the left hand side of the equation by subtracting 6x from both sides.
−8x+21−6x=1

Add −8x and −6x to get −14x.
−14x+21=1

Move 21 to the right hand side of the equation by subtracting 21 from both sides.
−14x=−21+1

Add −21 and 1 to get −20.
−14x=−20

Divide each term in the equation by −14.
x=10/7

x is equal to 10/7 or 1 3/7